Avaliação de procedimentos para quantificação espectrofotométrica de flavonoides totais em folhas de Bauhinia forficata Link - Graziella Silvestre Marques; Rebeka Priscila Maranhão Monteiro; Waleska de Figueirêdo Leão; Magaly Andreza Marques Lyra; Monize Santos Peixoto; Pedro José Rolim-Neto; Haroudo Sátiro Xavier; Luiz Alberto de Lira Soares (Química Nova, 2012)
Interest in analytical methods for quality control of herbal drugs has grown sharply due to the scarcity of monographs in official manuals. Thus, the aim of the present study was to evaluate analytical procedures for quantitative determination of flavonoids from leaves of Bauhinia forficata Link (pata-de-vaca). Two procedures for quantification of total flavonoids (with and without acid hydrolysis) by spectrophotometry were tested. The proposed methods proved to be specific, sensitive, precise, accurate and robust, being suitable for routine laboratory use.